Increasing Timely Follow-up with Pediatric Orthopaedic Fracture Care: A Quality Improvement Project. Issue 1 (January 2022) - Bishop, Courtney; Dolan, Kevin; Balch Samora, Julie
Abstract : Background: Timely follow-up for radiographic and clinical evaluation with an orthopaedic specialist is critical in avoiding potential complications after pediatric long bone fractures. At our large, tertiary care, pediatric hospital, the baseline rate of timely follow-up after evaluation of reduced fractures in the emergency department was 74.4%. We tested the hypothesis that we could use quality improvement (QI) methods to increase the rate of timely follow-up and improve patient care. Methods: A multidisciplinary QI program was implemented with education for staff; improvement of procedures; patient and family education; and a method to identify and provide resources for potential barriers to follow-up. Questionnaire results were documented and tabulated. Results: At the end of the QI program, patient rates of timely follow-up were 78.5%, compared with the 74.4% baseline. There was no statistical difference in follow-up between patients who received and completed the questionnaire and those who did not. For patients who did complete the questionnaire, there was no statistical difference between those who identified a barrier to follow-up and those who did not identify any difficulty with follow-up. Conclusions: Minimal improvement was noted on the percentage of timely follow-up in the orthopaedic clinic after reduction of a fracture. Although the interventions fell short of their goals, future opportunities exist for improvement of timely follow-up. Level of Evidence: Level II (prospective cohort study).